Private dental insurance expenditure in Brazil - Cascaes, Andreia Morales; Camargo, Maria Beatriz Junqueira de; Castilhos, Eduardo Dickie de; Silva, Alexandre Emídio Ribeiro; Barros, Aluísio J D (Revista de Saúde Pública, 2018)
OBJECTIVE: To quantify the household expenditure per capita and to estimate the percentage of Brazilian households that have spent with dental insurance. METHODS: We analyzed data from 55,970 households that participated in the research Pesquisa de Orçamentos Familiares in 2008–2009. We have analyzed the annual household expenditure per capita with dental insurance (business and private) according to the Brazilian states and the socioeconomic and demographic characteristics of the households (sex, age, race, and educational level of the head of the household, family income, and presence of an older adult in the household). RESULTS: Only 2.5% of Brazilian households have reported spending on dental insurance. The amount spent per capita amounted to R$5.10 on average, most of which consisted of private dental insurance (R$4.70). Among the characteristics of the household, higher educational level and income were associated with higher spending. São Paulo was the state with the highest household expenditure per capita (R$10.90) and with the highest prevalence of households with expenditures (4.6%), while Amazonas and Tocantins had the lowest values, in which both spent less than R$1.00 and had a prevalence of less than 0.1% of households, respectively. CONCLUSIONS: Only a small portion of the Brazilian households has dental insurance expenditure. The market for supplementary dentistry in oral health care covers a restricted portion of the Brazilian population.